2011
DOI: 10.1029/2011gl046840
|View full text |Cite
|
Sign up to set email alerts
|

Surface wave tomography across Afar, Ethiopia: Crustal structure at a rift triple-junction zone

Abstract: The Afar Depression in northeast Africa contains the rift triple‐junction between the Nubia, Arabia and Somalia plates. We analyze Rayleigh wave group velocity from 250 regional earthquakes recorded by 40 broadband stations to study the crustal structure across Afar and adjacent plateau regions in northern Ethiopia. The dispersion velocities are inverted to obtain surface wave tomographic maps for periods between 5 and 25 seconds, sensitive to approximately the top 30 km of the lithosphere. The tomographic map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
6
23
0
Order By: Relevance
“…There are broad pronounced low velocity features over the area of our profiles from both surface waves of up to 12 s period (Guidarelli et al 2011) and P n studies (Stork et al 2013). High upper crustal seismic anisotropy values are attributed to melt pockets in cracks orientated parallel to the rift segment axes .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…There are broad pronounced low velocity features over the area of our profiles from both surface waves of up to 12 s period (Guidarelli et al 2011) and P n studies (Stork et al 2013). High upper crustal seismic anisotropy values are attributed to melt pockets in cracks orientated parallel to the rift segment axes .…”
Section: Discussionmentioning
confidence: 84%
“…It was thus interpreted as a porous melt channel rapidly delivering magma to the crust (Key et al 2013). In the part of Afar we investigated, the highest mantle conductivities were also offset from the rift axes and the base of the crust and uppermost mantle were seismically slow (Guidarelli et al 2011;Stork et al 2013); we did not have the depth penetration to determine whether these broad conductors become more laterally confined at depth. Magma is stored in the crust in both axial and off-axis (4-8 km from the axis) locations beneath the East Pacific Rise; in the latter, the magma is stored in partially molten lower crustal sills (Canales et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…S-wave velocities are more sensitive to melt than P-waves. The lower crust and upper mantle beneath Afar contain appreciable amounts of melt, giving rise to high V p /V s (>2.0) deduced from receiver function studies , and low S-wave velocities derived from surface-wave studies (Guidarelli et al, 2011). The differences in P-wave and S-wave anomalies on June 2, 2015 geology.gsapubs.org Downloaded from in the presence of melt are even more pronounced when melt retains a preferential orientation, as has been proposed to explain mantle seismic anisotropy beneath the Main Ethiopian Rift and Red Sea Rift (Kendall et al, 2006;Gao et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…They saw a stratified anisotropic structure, but noted that their lateral resolution was of the order of 500 km. Guidarelli et al (2011) used regional Rayleigh waves to image the Afar region in finer detail, revealing a patchwork of stranded continental slivers surrounded by regions of low velocity, melt-rich material, a pattern not unlike that reported by Stork et al (2013). Using ambient noise imaging, Korostelev et al (2015) showed how magmatic processes are focused at the axial magmatic segments and also at the rift flanks.…”
Section: Geophysical Signature Of Lithospheric Meltmentioning
confidence: 97%